Physiologic expansion of human heart-derived cells enhances therapeutic repair of injured myocardium - Mount, Seth; Kanda, Pushpinder; Parent, Sandrine; Khan, Saad; Michie, Connor; Davila, Liliana; Chan, Vincent; Davies, Ross A; Haddad, Haissam; Courtman, David; Stewart, Duncan J; Davis, Darryl R (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Serum-free xenogen-free defined media and continuous controlled physiological cell culture conditions have been developed for stem cell therapeutics, but the effect of these conditions on the relative potency of the cell product is unknown. As such, we conducted a head-to-head comparison of cell culture conditions on human heart explant-derived cells using established in vitro measures of cell potency and in vivo functional repair. Methods Heart explant-derived cells cultured from human atrial or ventricular biopsies within a serum-free xenogen-free media and a continuous physiological culture environment were compared to cells cultured under traditional (high serum) cell culture conditions in a standard clean room facility. Results Transitioning from traditional high serum cell culture conditions to serum-free xenogen-free conditions had no effect on cell culture yields but provided a smaller, more homogenous, cell product with only minor antigenic changes. Culture within continuous physiologic conditions markedly boosted cell proliferation while increasing the expression of stem cell-related antigens and ability of cells to stimulate angiogenesis. Intramyocardial injection of physiologic cultured cells into immunodeficient mice 1 week after coronary ligation translated into improved cardiac function and reduced scar burden which was attributable to increased production of pro-healing cytokines, extracellular vesicles, and microRNAs. Conclusions Continuous physiological cell culture increased cell growth, paracrine output, and treatment outcomes to provide the greatest functional benefit after experimental myocardial infarction.